2008
DOI: 10.2190/de.38.3.e
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Drinking Behavior and Access to Alcohol between Native American and White Adolescents

Abstract: We investigated differences in drinking behaviors and sources of alcohol among Native American (n=361) and White adolescents (n=1,735), ages 11 to 19. Native American youth were more likely to have consumed alcohol in their lifetime and been intoxicated in the last 30 days than Whites. Native American drinkers were almost twice as likely to have gotten alcohol from an adult and twice as likely to have obtained alcohol from someone under 21. White drinkers were four times as likely to have obtained alcohol from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…This study is consistent with previous research in fi nding that Native American youths were more likely than White youths to have consumed alcohol in their lifetime and in the past 30 days, and to report heavy episodic drinking (e.g., Bachman et al, 1991;Friese and Grube, 2008;Spear et al, 2005). Retail alcohol-outlet density was not signifi cantly related to drinking in any of the analyses.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study is consistent with previous research in fi nding that Native American youths were more likely than White youths to have consumed alcohol in their lifetime and in the past 30 days, and to report heavy episodic drinking (e.g., Bachman et al, 1991;Friese and Grube, 2008;Spear et al, 2005). Retail alcohol-outlet density was not signifi cantly related to drinking in any of the analyses.…”
Section: Discussionsupporting
confidence: 90%
“…Rather, our data show that the Native American youths in our sample do not have the same access to alcohol at home as do White youths. A similar pattern was found in our previous study of Native American and White youths in Wisconsin (Friese and Grube, 2008). It may be that Native American parents are more proactive about preventing youth access to alcohol in the home.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Predictors of consistent alcohol use included alcohol expectancies, sensation seeking, other risky behaviors, and parental problems with alcohol. Friese and Grube (2009) examined direct community-level influences and reported that compared with Whites, NA youth drinkers were twice as likely to have gotten alcohol from an adult and from someone under age 21, and less likely to have obtained alcohol from their parents. Results by Friese and colleagues (2015) indicate that higher drinking among NA youth may be accounted for by lower school involvement, weaker neighborhood antidrug norms, greater neighborhood disorganization, and lower levels of police enforcement.…”
Section: T His Study Provides New Information Tomentioning
confidence: 99%
“…Not only do adolescents have easy access to alcohol at home, some parents actively supply alcohol to their underage children (Friese & Grube, 2008), and some parents let children consume alcohol within their company (Mayer et al, 1998).…”
Section: Social Availabilitymentioning
confidence: 99%